Influence of obesity levels in diabetic pregnant women and their newborns (Research, Society and Development, 2023)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia due to defects in insulin secretion or action, or both. It can be classified as type 1 DM, type 2 DM, and gestational diabetes mellitus (GDM). By using two parallel diagnostic tests, a group of pregnant women with mild gestational hyperglycemia (GH) was identified, which showed a positive screening for diabetes through the glycemic profile (GP) but a negative diagnosis for DM. Pregnant women with GH exhibit maternal and perinatal repercussions similar to diabetic groups, such as glucose intolerance, insulin resistance, obesity, and fetal macrosomia. The objective was to evaluate the different degrees of obesity in diabetic and GH pregnant women, seeking to relate them to maternal-fetal complications and fetal malformations. To achieve this, data previously collected from pregnant women and their newborns were used, inserted into a database from the Hospital das Clínicas, Faculdade de Medicina de Botucatu/Unesp, with approval from the ethics committee. After diagnosing obesity using the body mass index (BMI), it was correlated with initial and final maternal conditions and with variables of the newborns (body weight and newborn ponderal index). A positive correlation was found between initial and final BMI and newborn weight, indicating that the higher the maternal BMI at both ends of pregnancy, the greater the newborn weight and ponderal index. Considering the gestational alterations, diagnosis of GDM and GH in pregnant women, it is concluded that increased maternal weight directly influences increased newborn weight and perinatal outcomes.